Behavior Swelling-Shrinkage of Residual Soils as Chemically Stabilized - Moh. Muntaha; Fitria Wahyuni; Masyitah binti Nujid (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The soils of Balikpapan belong to the soft to medium soil group, consisting of residual and sedimentary soils. Residual soil generally has granules in the silty soil group. Residual soil has a high shear strength when dry, shrinks when wet, and has a large capacity, so this soil has a low bearing capacity when wet. Potential swelling and shrinkage can occur due to changes in soil volume caused by changes in the level of liquid in the soil cavity. Soil swelling and shrinkage can cause damage to the building structure. Helmut is a blend of chemicals that act as soil stabilizers, such as lime and polymers. Helmut is a new chemical ingredient being developed by researchers. The soil stabilization method was to mix the soil with additives such as Helmut. The mixing of the original Balikpapan soil with the Helmut additive in the laboratory was manually done by adding the additive materials at 1, 2, 4, 6, 8, and 10% to the dry weight ratio of the soil and the optimum moisture content. The results showed that the Balikpapan soil had good physical and mechanical properties; the potential for shrinkage was also low, as indicated by a low activity value of A = 0.365 and a shrinkage limit of 16.99%. Soil stabilized with Helmut additives showed improved physical and mechanical properties, and soil activity decreased.